The radiative impact of clouds on the response of the midlatitude circulation to global warming - Albern, Nicole Brigitte Silvia (KIT-Bibliothek, Karlsruhe, 2021)
Clouds and the midlatitude circulation are strongly coupled via radiation. Previous work showed that about half of the annual-mean zonal-mean jet stream and storm track responses to global warming can be attributed to cloud-radiative changes. In this thesis, we investigate the impact of cloud-radiative changes on the global warming response of the midlatitude jet streams and storm tracks across seasons and regions with special focus on the North Atlantic, North Pacific and Southern Hemisphere. To this end, we perform global simulations with the atmospheric component of the ICOsahedral Nonhydrostatic (ICON) model in a present-day setup. We prescribe sea-surface temperatures (SST) to isolate the impact of changes in atmospheric cloud-radiative heating on the midlatitude circulation, and mimic global warming by a uniform 4K or spatially-varying SST increase. We use the cloud-locking method to decompose the midlatitude circulation response into contributions from changes in cloud-radiative properties and from changes in SST. In the first part of the thesis, we investigate the impact of global cloud-radiative changes on the response of the midlatitude jet streams and storm tracks to global warming. In the annual mean, cloud-radiative changes contribute one to two thirds to the poleward jet shift in all three ocean basins and support the jet strengthening in the North Atlantic and Southern Hemisphere. Cloud-radiative changes also impact the storm track, but the impact is more diverse across the three ocean basins. The cloud-radiative impact on the North Atlantic and North Pacific jet streams varies little from season to season in absolute terms, whereas its relative importance changes over the course of the year. In the Southern Hemisphere, cloud-radiative changes strengthen the jet stream in all seasons, whereas their impact on the jet shift is limited to austral summer and fall. The cloud-radiative impact is largely zonally symmetric and independent of whether global warming is mimicked by a uniform 4K or ...